Cortisol profiles differ by race/ethnicity among young sexual minority men. (January 2017) - Cook, Stephanie H.; Juster, Robert-Paul; Calebs, Benjamin J.; Heinze, Justin; Miller, Alison L.
Highlights: Race/Ethnicity is related to stress physiology in sexual minority men. Compared to White sexual minority men, Black sexual minority men have elevated evening cortisol levels. Compared to White sexual minority males, Black sexual minority males have a flatter diurnal cortisol curve. Abstract: Much of the extant scientific research examining hypothalamic-pituitary-adrenal (HPA)-axis functioning is conducted among White heterosexuals. Very little research examines HPA-axis functioning between different minority groups. Individuals who identify as both sexual and racial minorities may experience increased stigma and discrimination that can affect HPA-axis functioning. In the current study, we examined diurnal cortisol rhythm in young White gay men (WGM) compared to young Black gay men (BGM). The sample consisted of 70 healthy gay men (mean [SD] age = 22.9 [3.2]: 68% White and 38% Black) who collected four saliva samples daily for five days. Repeated measures analysis of covariance and post-hoc tests revealed that BGM had higher cortisol levels than WGM in the evening. Secondary analyses revealed no significant group differences for the cortisol awakening response or systemic output throughout the day. However, BGM compared to WGM had a lower drop from peak (morning) to lowest (evening) cortisol concentrations. Taken together, these findings reveal a flatter diurnal cortisol rhythm among BGM compared to WGB. The functional significance of these preliminary findings must be explored further with assessment of psychosocial factors among sexual minorities at the intersection of multiple identities. In summary, we expand health disparities research aimed at delineating sexual minority and race/ethnic variation in stress physiology.